The Effect Of Papaverine On Mechanical Activity in Ileal Smooth Mascle Of Hedgehogs - Saied, F. N.; Gathwan, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This is the first time that the mechanical activity of Hedgehog i lealsmooth muscle is a regular spontaneous contraction to be reported. It was  found  that  the different concent1Â·ations of  papaverine exerted different dcgces of inhibition on ileal smooth muscle. The minimumeffective  dose  was  (0.05)  mM.  Different  concentration  of acetylcholine and KCI caused tonic contraction in this kind of smooth muscle. High concentration of papaverine caused inst